The Relationship between Mothering Patterns and the Incidence of Stunting: A Literature Review - Rahma, Andi Anugrah; Kurniati, Yessy (Unihealth Community Research, 2026)
Stunting is one of the global health issues that remains a major challenge, especially in developing countries such as Indonesia. Although its prevalence has decreased slightly from 21.6% in 2022 to 21.5% in 2023, this figure is still far from the national target of 14%. Stunting is caused by chronic malnutrition and recurrent infections, especially during the first 1,000 days of life (HPK). One of the factors contributing to stunting is maternal parenting, particularly in terms of nutritional fulfillment, psychosocial stimulation, and child care. This study aims to review the relationship between maternal parenting styles and the incidence of stunting through a literature review approach. The method used is a qualitative descriptive study by examining 10 quantitative research articles with a cross-sectional design selected from Google Scholar and PubMed based on inclusion criteria. The results show that most articles state that there is a significant relationship between maternal parenting and the incidence of stunting. Democratic and responsive parenting contributes to the prevention of stunting, while inappropriate parenting increases the risk. Therefore, strengthening parenting education is an important strategy in efforts to reduce stunting in Indonesia.